Volcanic activity on the Kuril Islands in 2023 - @Degterev, Artem V.; Chibisova, Marina V. (Геосистемы переходных зон)
Ebeko and Chikurachki volcanoes, located on Paramushir Island (the Northern Kuril Islands), were in a state of eruption in 2023. During that year, Ebeko volcano showed moderate volcanic activity typical of its recent years, characterized by frequent phreatic and phreatomagmatic ash explosions. According to video surveillance data, a total of 675 emissions to a height of 1.5 to 4.5 km above sea level were recorded, 293 of which were up to 3 km above sea level and higher. As in the previous years, the maximum activity (in terms of the number and height of emissions) was observed in the period from June to August (244 ash emissions, 94 of which were up to 3 km above sea level or higher). The explosions were more frequent from January to April (59 emissions in January and 64 emissions in March) and in December (56 emissions). Another explosive eruption of Chikurachki volcano occurred from 28.01.23 to 8.02.2023. The eruptive events were characterized by moderate volcanic activity: both occasional explosions and phases of relatively quiet and prolonged emission of ash and gas mixture were observed. At least 8 emissions to a height of 2.5–4.5 km above sea level were recorded, similar in their nature to the previous 5 episodes of explosive volcanic activity that occurred throughout 2022.